High-strength concrete, well lid and preparation method of high-strength concrete and well lid

By modifying the steel fibers with aminosilane coupling agent and epoxy resin coating, a mucoplating layer is formed, and by optimizing the aggregate grading, the problems of steel fibers being unevenly bonded and dispersed in concrete are solved, which significantly improves the compressive strength and bearing capacity of the concrete.

CN119504205APending Publication Date: 2025-02-25GUANGDONG GUANGZE IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411694598.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Among the existing high-strength steel fiber concrete, the bond between steel fibers and concrete mainly depends on physical bonding, which leads to easy extraction of steel fibers; at the same time, steel fibers are easily adsorbed to form a cluster, which is difficult to disperse evenly, and cannot fully exert the reinforcement role.

Method used

By using aminosilane coupling agent and epoxy resin coating to modify the steel fibers to form a mucogenic film layer to improve the adhesion performance between the steel fibers and concrete; at the same time, by optimizing the aggregate grading, the modified steel fibers are dispersed to achieve uniform dispersion.

Benefits of technology

It effectively improves the bonding stability of steel fibers and concrete, prevents steel fibers from being pulled out, promotes their uniform dispersion, and significantly improves the compressive strength and bearing capacity of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005151808680000091
    Figure BDA0005151808680000091
  • Figure BDA0005151808680000101
    Figure BDA0005151808680000101
Patent Text Reader

Abstract

The invention discloses high-strength concrete, a well lid and a preparation method of the well lid, and relates to the field of building materials. The high-strength concrete comprises cement, coarse aggregate, fine aggregate, modified steel fibers, a polycarboxylic acid water reducer and water. Wherein the coarse aggregate comprises broken stones with the continuous grading of 5-8 mm and broken stones with the continuous grading of 10-16 mm; the fine aggregate adopts medium-coarse sand with the particle size range of 1.8-2.2 mm; the preparation raw materials of the modified steel fiber comprise an amino silane coupling agent, an epoxy resin coating and steel fiber, and the preparation raw materials of the epoxy resin coating comprise bisphenol A epoxy resin, nanoparticles, hydroxy acrylic resin, a tertiary amine catalyst and a curing agent. According to the modified steel fiber, the reinforcing effect of the steel fiber on a concrete matrix can be fully exerted, so that concrete which is high in pressure resistance and bearing capacity and especially suitable for well lid manufacturing is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and in particular to a high-strength concrete and a manhole cover and a preparation method thereof. Background Art

[0002] In many engineering fields such as construction and municipal engineering, steel fiber concrete has been widely used due to its excellent performance. Among them, steel fiber concrete is a new type of multi-phase composite material formed by adding randomly distributed short steel fibers to ordinary concrete. It combines the high strength and high toughness of steel fibers with the compressive properties of concrete, making the concrete material better than ordinary concrete in terms of tensile resistance, bending resistance, shear resistance, impact resistance and fatigue resistance. At present, steel fiber concrete materials are widely used in the preparation of road manhole covers.

[0003] However, the existing high-strength steel fiber concrete has the following two difficulties: (1) The bonding between steel fiber and concrete is mainly physical bonding, that is, the stress is transferred at the interface between the two through friction shear force. This bonding method is relatively weak. When subjected to external force, the steel fiber is easily pulled out of the concrete matrix instead of playing its due reinforcing role.

[0004] (2) Steel fibers are easily adsorbed together due to friction, static electricity, etc., which makes it easy for steel fibers to clump and difficult to evenly disperse in concrete. The above two points make it impossible for steel fibers to fully play their due reinforcing role. Therefore, it is necessary to provide a concrete with good steel fiber dispersion and excellent adhesion between steel fibers and concrete, so as to fully play the reinforcing role of steel fibers, further improve the strength and other properties of steel fiber concrete, and make steel fiber concrete more advantageous in application. Summary of the invention

[0005] In order to improve the problem in the related art that the reinforcing effect of steel fibers cannot be fully exerted, the present application provides a high-strength concrete and a manhole cover and a preparation method thereof.

[0006] In the first aspect, the high-strength concrete provided in the present application adopts the following technical solution: A high-strength concrete comprises 475-485 parts by weight of cement, 715-725 parts by weight of coarse aggregate, 1075-1085 parts by weight of fine aggregate, 115-125 parts by weight of modified steel fiber, 9.2-9.8 parts by weight of polycarboxylate water-reducing agent and 165-170 parts by weight of water; wherein the coarse aggregate comprises crushed stone with a continuous gradation of 5-8 mm and crushed stone with a continuous gradation of 10-16 mm, and the weight ratio of the crushed stone with a continuous gradation of 5-8 mm to the crushed stone with a continuous gradation of 10-16 mm is 1:(3-4); the fine aggregate is medium-coarse sand with a particle size range of 1.8-2.2 mm; The raw materials for preparing the modified steel fiber include aminosilane coupling agent, epoxy resin coating and steel fiber. The raw materials for preparing the epoxy resin coating include bisphenol A epoxy resin, nanoparticles, hydroxyl acrylic resin, tertiary amine catalyst and curing agent in a weight ratio of 100: (0.55-0.75): (10-15): (1-2): (20-25).

[0007] In the present application, high-strength concrete is made of cement, crushed stone of specific gradation, fine aggregate of specific particle size range, modified steel fiber, polycarboxylic acid water reducer and water. Among them, the modified steel fiber is obtained by modifying the steel fiber with aminosilane coupling agent and epoxy resin coating. Specifically, the surface of the steel fiber is first modified with aminosilane coupling agent, and then the epoxy resin coating is sprayed on the surface of the surface-modified steel fiber. After the epoxy resin coating is cured, a layer of adhesion film is formed on the surface of the steel fiber, which can improve the bonding performance between the steel fiber and the concrete and prevent the problem of the steel fiber being pulled out of the concrete. In addition, through the optimized aggregate gradation, the massed modified steel fiber is broken up by the aggregate, so that the modified steel fiber is evenly dispersed in the high-strength concrete, which is conducive to the modified steel fiber to give full play to the reinforcing effect, thereby obtaining a concrete with high compressive strength, strong bearing capacity, and especially suitable for the production of manhole covers.

[0008] A crucial point of this application is that the adhesion stability of epoxy resin coating to the steel fiber surface is improved by introducing aminosilane coupling agent. At the same time, the epoxy resin coating is made of bisphenol A epoxy resin, nanoparticles, hydroxy acrylic resin, tertiary amine catalyst and curing agent in a specific ratio, which can improve the structural stability and impact resistance of the film layer on the surface of the modified steel fiber. Through the cooperation of the two, the film layer on the surface of the modified steel fiber is effectively prevented from falling off under the impact of aggregates, which causes the problem that the modified steel fiber cannot be evenly dispersed, and the bonding stability between the modified steel fiber and the concrete matrix is ​​effectively improved.

[0009] In some specific embodiments, the steel fiber is a straight steel fiber with a length ranging from 10 to 20 mm.

[0010] In the present application, the steel fibers are straight steel fibers with a length range of 10-20 mm, which is conducive to the uniform dispersion of the modified steel fibers in the high-strength concrete, further reducing the aggregation phenomenon between the modified steel fibers, thereby further improving the compressive strength and bearing capacity of the concrete.

[0011] In some specific embodiments, the epoxy value of the bisphenol A epoxy resin is 0.55-0.56, and the hydroxyl value of the hydroxy acrylic resin is 85-95 mgKOH / g based on solid.

[0012] In the present application, the epoxy value of the bisphenol A epoxy resin is preferably 0.55-0.56, and the hydroxyl value (solid basis) of the hydroxy acrylic resin is 85-95 mgKOH / g, which is beneficial to further improve the stability of the surface film layer of the modified steel fiber and promote further uniform dispersion of the modified steel fiber.

[0013] In some specific embodiments, the nanoparticles are at least one of nano-silicon dioxide and nano-calcium carbonate.

[0014] In some specific embodiments, the curing agent is an alicyclic amine curing agent.

[0015] In the present application, the curing agent is preferably an alicyclic amine curing agent, which can impart better toughness and chemical corrosion resistance to the surface film of the modified steel fiber, which is beneficial to further improve the structural stability of the surface film of the modified steel fiber, promote the uniform dispersion of the modified steel fiber and improve the bonding strength between the modified steel fiber and the concrete matrix, thereby effectively improving the compressive strength and bearing capacity of the concrete.

[0016] In some specific embodiments, the preparation method of the epoxy resin coating is as follows: Bisphenol A epoxy resin, hydroxy acrylic resin and tertiary amine catalyst are mixed evenly, then heated to 200-220°C for reaction for 1-2 hours, then cooled to room temperature, nanoparticles and curing agent are added, stirred evenly, and epoxy resin coating is obtained.

[0017] In some specific embodiments, the method for preparing the modified steel fiber comprises the following steps: The aminosilane coupling agent is prepared into an ethanol solution with a mass concentration of 1-2%, and then the solution is added into the steel fiber, and the solution is ball-milled at a speed of 200-300 r / min for 1-2 hours, and then the liquid is separated, and the solid is dried to obtain the aminosilane coupling agent modified steel fiber; The epoxy resin coating is evenly sprayed on the surface of the aminosilane coupling agent modified steel fiber, and then a curing reaction is carried out at 60-80° C. to obtain the modified steel fiber.

[0018] In the present application, the adhesion stability of the epoxy resin coating on the steel fiber surface is first improved by introducing an aminosilane coupling agent, and then the epoxy resin coating is prepared by using a specific ratio of bisphenol A epoxy resin, nanoparticles, hydroxy acrylic resin, tertiary amine catalyst and curing agent to improve the structural stability and impact resistance of the film layer on the surface of the modified steel fiber, effectively preventing the film layer on the surface of the modified steel fiber from falling off under the impact of the aggregate, causing the modified steel fiber to be unable to be evenly dispersed, and also effectively improving the bonding stability between the modified steel fiber and the concrete matrix.

[0019] In some specific embodiments, the weight ratio of the steel fiber to the ethanol solution with a mass concentration of 1-2% of the aminosilane coupling agent is 1:(8-10).

[0020] In some specific embodiments, the weight ratio of the aminosilane coupling agent modified steel fiber to the epoxy resin coating is 10:(1-1.5).

[0021] In the present application, the weight ratio of the aminosilane coupling agent modified steel fiber to the epoxy resin coating is controlled to be 10:(1-1.5), which can achieve uniform coating of the surface of the modified steel fiber. At the same time, the film layer on the surface of the modified steel fiber will not be too thick, which is conducive to the firm bonding of the modified steel fiber and the concrete matrix.

[0022] In the second aspect, the present application provides a manhole cover adopting the following technical solution: A manhole cover comprises a steel frame portion and a concrete cover portion filled in the steel frame, wherein the concrete cover portion is made of any one of the high-strength concretes described above.

[0023] In the present application, the concrete cover body of the manhole cover is made of any one of the above-mentioned high-strength concretes, which is conducive to obtaining a manhole cover with high compressive strength and strong bearing capacity.

[0024] In a third aspect, the present application provides a method for preparing a manhole cover using the following technical solution: A method for preparing a manhole cover, used for preparing the above-mentioned manhole cover, comprises the following steps: The coarse aggregate, fine aggregate and modified steel fiber are stirred evenly at a stirring speed of 65-75 r / min according to the proportion to obtain a premix; the polycarboxylate water reducer is added into water, stirred evenly at a stirring speed of 15-20 r / min, and then cement is added and stirred evenly to obtain cement slurry; Add premix to cement slurry, stir at a stirring speed of 45-55r / min until uniformly dispersed to obtain high-strength concrete; put a steel skeleton into a mold, and then fill the steel skeleton with high-strength concrete, vibrate evenly, and then maintain to obtain a manhole cover.

[0025] In the present application, the coarse aggregate, fine aggregate and modified steel fiber are first mixed evenly at a mixing speed of 65-75r / min, and then the cement slurry is prepared. Subsequently, the premix is ​​added to the cement slurry and the mixing is controlled at a mixing speed of 45-55r / min. This can achieve uniform dispersion of the modified steel fiber without destroying the membrane structure on the surface of the steel fiber, which is beneficial to promoting the uniform dispersion of the modified steel fiber and improving the bonding strength between the modified steel fiber and the concrete matrix, and can improve the compressive strength and bearing capacity of the manhole cover.

[0026] In summary, this application at least includes the following beneficial technical effects: (1) In the present application, the modified steel fiber is obtained by modifying the steel fiber with an aminosilane coupling agent and an epoxy resin coating. Specifically, the surface of the steel fiber is first modified with an aminosilane coupling agent, and then the epoxy resin coating is sprayed on the surface of the surface-modified steel fiber. After the epoxy resin coating is cured, a layer of adhesion-enhancing film is formed on the surface of the steel fiber, which can improve the bonding performance between the steel fiber and the concrete and prevent the problem of the steel fiber being pulled out of the concrete. In addition, through the optimized aggregate grading, the aggregate is used to break up the lumpy modified steel fiber, so that the modified steel fiber is evenly dispersed in the high-strength concrete, which is conducive to the modified steel fiber to fully exert its reinforcing effect, thereby obtaining a concrete with high compressive strength and strong bearing capacity, which is particularly suitable for the production of manhole covers.

[0027] (2) In the present application, the curing agent used in the epoxy resin coating is preferably an alicyclic amine curing agent, which can give the modified steel fiber surface film layer better toughness and chemical corrosion resistance, which is beneficial to further improve the structural stability of the modified steel fiber surface film layer, promote the uniform dispersion of the modified steel fiber and the improvement of the bonding strength between the modified steel fiber and the concrete matrix, thereby effectively improving the compressive strength and bearing capacity of the concrete. DETAILED DESCRIPTION

[0028] The present application is further described below in conjunction with specific experiments. Example

[0029] [Example 1] A high-strength concrete is prepared from 475 g of cement, 715 g of coarse aggregate, 1075 g of fine aggregate, 115 g of modified steel fiber, 9.2 g of polycarboxylate water-reducing agent and 165 g of water.

[0030] Among them, the cement used is P.O42.5R cement.

[0031] The coarse aggregate includes crushed stone with a continuous grading of 5-8 mm and crushed stone with a continuous grading of 10-16 mm, and the weight ratio of the crushed stone with a continuous grading of 5-8 mm to the crushed stone with a continuous grading of 10-16 mm is 1:3.

[0032] The fine aggregate is medium-coarse sand with a particle size range of 1.8-2.2mm.

[0033] The preparation method of the modified steel fiber comprises the following steps: S1. The aminosilane coupling agent KH550 and an ethanol solution with an ethanol mass concentration of 20% are mixed in a weight ratio of 1:99 to prepare an ethanol solution with an aminosilane coupling agent mass concentration of 1%, and then steel fibers are added. The weight ratio of the steel fibers to the ethanol solution with an aminosilane coupling agent mass concentration of 1% is 1:10, and the steel fibers are straight steel fibers with a length range of 25-30 mm (Chongqing Zhulu New Building Materials Co., Ltd.). Then, the steel fibers are ball-milled at a speed of 200 r / min for 2 h, and then the liquid is separated. After the solid is dried, the aminosilane coupling agent-modified steel fibers are obtained; S2. Evenly mix 100g of bisphenol A epoxy resin with an epoxy value of 0.55-0.56 (Hubei Maidewu Biotechnology Co., Ltd.), 10g of hydroxyl acrylic resin with a hydroxyl value of 85-95mgKOH / g in terms of solid (Nantong Fangxin Chemical Co., Ltd. FX-9003), and 1g of tertiary amine catalyst bis(dimethylaminoethyl) ether, then heat to 200°C to react for 2h, then cool to room temperature, add 0.75g of nano-calcium carbonate and 25g of chain amine curing agent 1,6-hexanediamine, stir evenly to obtain epoxy resin coating.

[0034] S3. 20 g of epoxy resin coating is evenly sprayed on the surface of 200 g of aminosilane coupling agent modified steel fiber, and then a curing reaction is carried out at 60° C. to obtain modified steel fiber.

[0035] The polycarboxylate water reducer used was BASF polycarboxylate water reducer F10.

[0036] In this embodiment, a method for preparing high-strength concrete includes the following steps: The coarse aggregate, fine aggregate and modified steel fiber are stirred uniformly at a stirring speed of 65 r / min according to the proportion to obtain a premix; the polycarboxylate water reducer is added into water, stirred uniformly at a stirring speed of 15 r / min, and then cement is added and stirred uniformly to obtain a cement slurry; The premix is ​​added to the cement slurry and stirred at a stirring speed of 55 r / min until uniformly dispersed to obtain high-strength concrete.

[0037] [Example 2] A high-strength concrete is prepared from 485 g of cement, 725 g of coarse aggregate, 1085 g of fine aggregate, 125 g of modified steel fiber, 9.8 g of polycarboxylate water-reducing agent and 170 g of water.

[0038] Among them, the cement used is P.O42.5R cement.

[0039] The coarse aggregate includes crushed stone with a continuous grading of 5-8 mm and crushed stone with a continuous grading of 10-16 mm, and the weight ratio of the crushed stone with a continuous grading of 5-8 mm to the crushed stone with a continuous grading of 10-16 mm is 1:4.

[0040] The fine aggregate is medium-coarse sand with a particle size range of 1.8-2.2mm.

[0041] The preparation method of the modified steel fiber comprises the following steps: S1. The aminosilane coupling agent KH550 and an ethanol solution with an ethanol mass concentration of 20% are mixed uniformly in a weight ratio of 2:98 to prepare an ethanol solution with an aminosilane coupling agent mass concentration of 2%, and then steel fibers are added. The weight ratio of the steel fibers to the ethanol solution with an aminosilane coupling agent mass concentration of 2% is 1:8. The steel fibers are straight steel fibers with a length range of 25-30 mm (Chongqing Zhulu New Building Materials Co., Ltd.). Then, the steel fibers are ball-milled at a speed of 300 r / min for 1 h, and then the liquid is separated. After the solid is dried, the aminosilane coupling agent-modified steel fibers are obtained; S2. Evenly mix 100g of bisphenol A epoxy resin with an epoxy value of 0.55-0.56 (Hubei Maidewu Biotechnology Co., Ltd.), 15g of hydroxyl acrylic resin with a hydroxyl value of 85-95mgKOH / g in terms of solid (Nantong Fangxin Chemical Co., Ltd. FX-9003), and 2g of tertiary amine catalyst bis(dimethylaminoethyl) ether, then heat to 220°C for reaction for 1h, then cool to room temperature, add 0.55g of nano-silica and 20g of chain amine curing agent 1,6-hexanediamine, stir evenly to obtain epoxy resin coating; S3. Evenly spray 30g of epoxy resin coating on the surface of 200g of aminosilane coupling agent modified steel fiber, and then perform curing reaction at 80°C to obtain modified steel fiber.

[0042] The polycarboxylate water reducer used was BASF polycarboxylate water reducer F10.

[0043] In this embodiment, a method for preparing high-strength concrete includes the following steps: The coarse aggregate, fine aggregate and modified steel fiber are mixed uniformly at a mixing speed of 75 r / min according to the proportion to obtain a premix; the polycarboxylate water reducer is added into water, mixed uniformly at a mixing speed of 20 r / min, and then cement is added and mixed uniformly to obtain a cement slurry; The premix is ​​added to the cement slurry and stirred at a stirring speed of 45 r / min until uniformly dispersed to obtain high-strength concrete.

[0044] [Example 3] A high-strength concrete, which differs from [Example 1] in that the curing agent adopts alicyclic amine curing agent isophorone diamine.

[0045] [Example 4] A high-strength concrete, which differs from [Example 3] in that in step S1 of preparing modified steel fibers, the steel fibers use straight steel fibers with a length range of 10-20 mm (Chongqing Zhulu New Building Materials Co., Ltd.).

[0046] [Example 5] A high-strength concrete, which differs from [Example 3] in that: in the S2 step of preparing the modified steel fiber, the reaction temperature is 180°C.

[0047] Comparative Example [Comparative Example 1] A concrete, which is different from [Example 1] in that: the coarse aggregate is all crushed stone with a continuous gradation of 10-16 mm.

[0048] [Comparative Example 2] A concrete, which is different from [Example 1] in that: all coarse aggregates are crushed stones with continuous grading of 5-8 mm.

[0049] [Comparative Example 3] A concrete, which is different from [Example 1] in that the modified steel fiber is different. In this comparative example, the preparation method of the modified steel fiber is as follows: S1. Evenly mix 100g of bisphenol A epoxy resin with an epoxy value of 0.55-0.56 (Hubei Maidewu Biotechnology Co., Ltd.), 10g of hydroxyl acrylic resin with a hydroxyl value of 85-95mgKOH / g in terms of solid (Nantong Fangxin Chemical Co., Ltd. FX-9003), and 1g of tertiary amine catalyst bis(dimethylaminoethyl) ether, then heat to 200°C to react for 2h, then cool to room temperature, add 0.75g of nano calcium carbonate and 25g of chain amine curing agent 1,6-hexanediamine, stir evenly to obtain epoxy resin coating.

[0050] S2. Spray 20 g of epoxy resin coating evenly on the surface of 200 g of straight steel fiber with a length range of 10-20 mm (Chongqing Zhulu New Building Materials Co., Ltd.), and then perform a curing reaction at 60° C. to obtain modified steel fiber.

[0051] [Comparative Example 4] A concrete, which differs from [Example 1] in that the preparation method of the modified steel fiber is different. In this comparative example, in step S2 of the preparation method of the modified steel fiber, the hydroxy acrylic resin is replaced by an equal mass of bisphenol A epoxy resin with an epoxy value of 0.55-0.56.

[0052] [Comparative Example 5] A concrete, which differs from [Example 1] in that the preparation method of the modified steel fiber is different. In this comparative example, nano calcium carbonate is not added in step S2 of the preparation method of the modified steel fiber.

[0053] [Comparative Example 6] A concrete, which differs from [Example 1] in that the modified steel fibers are replaced by an equal amount of straight steel fibers with a length range of 10-20 mm (Chongqing Zhulu New Building Materials Co., Ltd.).

[0054] Application Examples

Application Example 1

[0055] In this application example, the preparation method of the manhole cover is as follows: Put the steel frame into a rectangular mold, then pour high-strength concrete into the steel frame, vibrate it evenly, and then cure it to obtain the manhole cover.

[0056]

Application Example 2

[0057]

Application Example 3

[0058]

Application example 4

[0059]

Application Example 5

[0060] Comparative Application Examples

Comparative Application Example 1

[0061]

Comparative Application Example 2

[0062]

Comparative Application Example 3

[0063]

Comparative Application Example 4

[0064]

Comparative Application Example 5

[0065]

Comparative Application Example 6

[0066] Performance testing 1. Compressive strength: The concrete in each embodiment and comparative example was made into a test block with a size of 100 mm*100 mm*100 mm, and the compressive strength was tested after curing for 28 days. The test was performed with reference to Section 12 of GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". Nine concrete test blocks corresponding to each embodiment were randomly selected for testing, and the average compressive strength of the nine test blocks was recorded in Table 1.

[0067] 2. Bearing capacity: Refer to Appendix A of GB / T 26537-2011 "Steel Fiber Concrete Inspection Manhole Covers" to conduct crack load tests and failure load tests on the manhole covers in each application example and comparative application example, and record the results in Table 2 below. Among them, the crack width is the crack width of the manhole cover when the load is applied to the cracking load (200kN), and the crack width ≤0.20 is qualified. The crack load is the load value read when the maximum crack width reaches 0.2mm. The failure load is the maximum value displayed by the press after reading the crack load value and continuously applying the load at 2kN / s until the manhole cover is destroyed.

[0068] Table 1 Concrete compressive strength Sample Compressive strength / mPa Example 1 88.4 Example 2 89.3 Example 3 91.1 Example 4 91.8 Example 5 89.2 Comparative Example 1 85.6 Comparative Example 2 84.7 Comparative Example 3 84.8 Comparative Example 4 84.2 Comparative Example 5 85.3 Comparative Example 6 81.6 Table 2 Load-bearing capacity of manhole covers Combining Example 1 with Comparative Examples 1-6 and the test data in Table 1-2, it can be seen that the grading of coarse aggregate, the use of aminosilane coupling agent to pre-modify the steel fiber when preparing the modified steel fiber, and the use of the epoxy resin coating prepared in this application to spray the steel fiber pre-modified with the aminosilane coupling agent when preparing the modified steel fiber are all key technologies of this application to effectively improve the compressive strength of concrete and the bearing capacity of manhole covers to obtain qualified manhole covers.

[0069] Combining Example 3 with Example 1 and the test data in Table 1-2, it can be seen that after the curing agent in Example 3 is preferably an alicyclic amine curing agent, the compressive strength of the concrete and the bearing capacity of the manhole cover are further improved. The reason is that the curing agent is preferably an alicyclic amine curing agent, which can give the modified steel fiber surface film layer better toughness and chemical corrosion resistance, which is beneficial to further improve the structural stability of the modified steel fiber surface film layer, promote the uniform dispersion of the modified steel fiber and the improvement of the bonding strength between the modified steel fiber and the concrete matrix, thereby effectively improving the compressive strength and bearing capacity of the concrete.

[0070] Combining Example 4 with Example 3 and the test data in Table 1-2, it can be seen that when the steel fibers in Example 4 use straight steel fibers with a length range of 10-20 mm, the compressive strength of the concrete and the bearing capacity of the manhole cover are further improved. The reason is that the steel fibers use straight steel fibers with a length range of 10-20 mm, which is conducive to the uniform dispersion of the modified steel fibers in the high-strength concrete, further reducing the aggregation phenomenon between the modified steel fibers, thereby further improving the compressive strength and bearing capacity of the concrete.

[0071] Combining Example 5 with Example 3 and the test data in Table 1-2, it can be seen that the reaction temperature of bisphenol A epoxy resin, hydroxyl acrylic resin, and tertiary amine catalyst in the preparation process of modified steel fiber in Example 5 is not within 200-220°C, and the compressive strength of concrete and the bearing capacity of manhole cover are reduced, indicating that the reaction temperature of bisphenol A epoxy resin, hydroxyl acrylic resin, and tertiary amine catalyst is within 200-220°C, which is more conducive to improving the compressive strength of concrete and the bearing capacity of manhole cover.

[0072] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A high-strength concrete, characterized in that: The invention comprises 475-485 parts by weight of cement, 715-725 parts by weight of coarse aggregate, 1075-1085 parts by weight of fine aggregate, 115-125 parts by weight of modified steel fiber, 9.2-9.8 parts by weight of polycarboxylate water reducer and 165-170 parts by weight of water; The coarse aggregate includes crushed stone with a continuous grading of 5-8 mm and crushed stone with a continuous grading of 10-16 mm, and the weight ratio of the crushed stone with a continuous grading of 5-8 mm to the crushed stone with a continuous grading of 10-16 mm is 1:(3-4); the fine aggregate is medium-coarse sand with a particle size range of 1.8-2.2 mm; The raw materials for preparing the modified steel fiber include aminosilane coupling agent, epoxy resin coating and steel fiber. The raw materials for preparing the epoxy resin coating include bisphenol A epoxy resin, nanoparticles, hydroxy acrylic resin, tertiary amine catalyst and curing agent in a weight ratio of 100: (0.55-0.75): (10-15): (1-2): (20-25).

2. The high-strength concrete according to claim 1, characterized in that: The steel fibers are straight steel fibers with a length ranging from 10 to 20 mm.

3. The high-strength concrete according to claim 1, characterized in that: The epoxy value of the bisphenol A epoxy resin is 0.55-0.56, and the hydroxyl value of the hydroxy acrylic resin is 85-95 mgKOH / g based on solid.

4. The high-strength concrete according to claim 1, characterized in that: The curing agent is an alicyclic amine curing agent.

5. A high-strength concrete according to any one of claims 1 to 4, characterized in that: The preparation method of the epoxy resin coating is as follows: Bisphenol A epoxy resin, hydroxy acrylic resin and tertiary amine catalyst are mixed evenly, then heated to 200-220°C for reaction for 1-2 hours, then cooled to room temperature, nanoparticles and curing agent are added, stirred evenly, and epoxy resin coating is obtained.

6. A high-strength concrete according to any one of claims 1 to 4, characterized in that: The preparation method of the modified steel fiber comprises the following steps: The aminosilane coupling agent is prepared into an ethanol solution with a mass concentration of 1-2%, and then the solution is added into the steel fiber, and the solution is ball-milled at a speed of 200-300 r / min for 1-2 hours, and then the liquid is separated, and the solid is dried to obtain the aminosilane coupling agent modified steel fiber; The epoxy resin coating is evenly sprayed on the surface of the aminosilane coupling agent modified steel fiber, and then a curing reaction is carried out at 60-80° C. to obtain the modified steel fiber.

7. The high-strength concrete according to claim 6, characterized in that: The weight ratio of the steel fiber to the ethanol solution with a mass concentration of 1-2% of the aminosilane coupling agent is 1:(8-10).

8. The high-strength concrete according to claim 6, characterized in that: The weight ratio of the aminosilane coupling agent modified steel fiber to the epoxy resin coating is 10:(1-1.5).

9. A manhole cover, characterized in that: It comprises a steel frame part and a concrete cover part filled in the steel frame, and the concrete cover part is made of the high-strength concrete according to any one of claims 1-8.

10. A method for preparing a manhole cover, used for preparing a manhole cover as claimed in claim 9, characterized in that: The following steps are involved: The coarse aggregate, fine aggregate and modified steel fiber are uniformly mixed at a mixing speed of 65-75 r / min according to the proportion to obtain a premix; Add polycarboxylate water reducer into water, stir evenly at a stirring speed of 15-20 r / min, then add cement and stir evenly to obtain cement slurry; Add the premix to the cement slurry and stir at a stirring speed of 45-55r / min until it is evenly dispersed to obtain high-strength concrete; Put the steel frame into the mold, then fill the steel frame with high-strength concrete, vibrate it evenly, and then cure it to get the manhole cover.

Citation Information

Cited By

  • High-toughness and high-strength concrete, well lid and preparation method of well lid

    CN121554225A

  • High-toughness and high-strength concrete and well lid and preparation method thereof

    CN121554225B